Modified Si–Jun–Zi–Tang Attenuates Airway Inflammation in a Murine Model of Chronic Asthma by Inhibiting Teff Cells via the mTORC1 Pathway - Jin, Hualiang; Cai, Cui; Li, Bei; Jin, Weizhong; Xia, Junbo; Wang, Limin; Ma, Shenglin (Frontiers in Pharmacology, 2019)
Background: Modified Si-Jun-Zi-Tang (MSJZT), a multi-herb formulation, is frequently used in traditional Chinese medicine for patients during the remission stage of asthma. However, the pharmacological basis underlying the effects of MSJZT on asthma has yet to be elucidated. This study aims at evaluating the anti-asthmatic effects of MSJZT and investigating its possible mechanism. Methods: A chronic murine model of asthma was established by sensitization and repeated challenge with ovalbumin (OVA) in female BALB/c mice, followed with oral administration of MSJZT during remission, and then mouse were re-challenged by OVA. The chemical profile of MSJZT was analyzed by high-performance liquid chromatography. The characteristic features of allergic asthma, including airway hyperreactivity, histopathology, cytokine levels (IL-4, -5, -13, -17 and INF-γ), T regulatory (Treg) lymphocytes (Foxp3+CD4+CD25+) and T effector (Teff) lymphocytes (Foxp3−CD25+CD4+) in bronchoalveolar lavage fluid (BALF), and downstream proteins of mTORC1/2 signaling pathway were examined. Results: MSJZT markedly suppressed airway hyper-responsiveness to aerosolized methacholine, and reduced levels of IL-4, IL-5 and IL-13 in the BALF. Histological studies showed that MSJZT significantly reduced inflammatory infiltration in lung tissues. The percentage and absolute number of Teff cells were suppressed to a remarkable level by MSJZT without affecting Treg cells. Furthermore, MSJZT effectively inhibited the mTORC1 activity, but exerted limited effects on mTORC2, as assessed by the phosphorylation of the mTORC1 and mTORC2 substrates, S6 ribosomal protein, p70 S6 Kinase, mTOR S2481, and Akt, respectively. Conclusion: MSJZT attenuated chronic airway inflammation in a mouse model of asthma by inhibiting Teff cells, which occurred, at least in part, via modulation of the mTORC1 signaling pathway.